Vietnam - Thompson, C Michele (Acquiring Cross-Cultural Competence: Four Stages for Students of French vol I., 1998)
Keywords: dept.his

[Doctoral Dissertation Revision] - Kalk, Bruce H. (Fall;History., 1998)
Keywords: dept.his; faculty_collection; sabbatical_report

Leonard Bacon: New England Reformer and Antislavery Moderate - Davis, Hugh (Louisiana State University Press, 1998)
A nationally powerful reformer, editor, church leader, and author, Leonard Bacon (1802-1881) influenced the thinking of northern Protestants for more than fifty years. In this detailed biography, Hugh Davis offers the first scholarly treatment of Bacon's life and work. Convinced that he was obligated to educate the American people on a broad range of social, political, and theological issues, Bacon, a Congregational minister, actively sought to connect his church and community to the larger world of organized benevolence, religious and reform journalism, social activism, and scholarship. The son of New England Congregational missionaries to the native Americans on the Michigan frontier, he also endeavored to extend evangelical religion and New England ideas and institutions to the rest of the nation and even overseas. Offering new insights into the nineteenth-century Protestant ministry, the evangelical mentality, and the efforts of Americans in Bacon's generation to address the moral and social issues of their time, Leonard Bacon will prove an invaluable contribution to American religious, social, and political history.--(Source of description unspecified.)
Keywords: Bacon, Leonard, 1802-1881; Congregational churches; Biography; Clergy; United States; award_winner; dept.his; faculty_collection

Racism Matters - Wright, W. D. (Praeger, 1998)
This work offers a discussion of racism in America focusing on how white people have been affected by their own racism and how it impacts upon relations between blacks and whites. It draws attention to how racism is different from race and shows how whites have maintained a white racist America.
Keywords: Race relations; Racism; United States; United States; dept.his; faculty_collection

Plenty of barbarians, but no bird's milk: The depiction of Russia in German school books, 1890-1914 - Paddock, Troy R. E. (Internationale Schulbuchforschung, 1998)
This article examines the description of Russia in German history and geography textbooks. Nineteenth-century German pedagogical theory linked the natural sciences and the human sciences; the connection supplies further evidence of the perceived organic nature of the nation-state. Although regional and confessional differences among the German states affected the description of German history, the depiction of Russia was consistent. Russia was depicted as a barbaric, backward, and Asiatic empire. The implicit, and often explicit, comparison in the texts was between Russia and Germany. The description of a foreign power served to reinforce German national identity. Moreover, an examination of German geography and history textbooks reveals striking similarities between the perception of Russia in Germany and the Anglo-French depiction of the Near East. Dieser Aufsatz befaßt sich mit dem Rußlandbild in deutschen Schulbüchern für Geschichte und Geographie. Deutsche Pädagogik im 19. Jahrhundert verband die Naturwissenschaft mit der Geisteswissenschaft; diese Verbindung ist noch ein Beweis für die Auf- fassung des Nationalstaats als organisches Wesen. Obwohl regionale und konfessionelle Unterschiede unter den deutschen Ländern die Darstellung von deutscher Geschichte beeinflußten, war die Schilderung von Rußland übereinstimmend. Rußland wurde als ein barbarisches, rückständiges, asiatisches Reich gezeichnet. Der unausgesprochene, und manchmal doch ausgesprochene Vergleich in den Büchern galt Deutschland und Rußland. Die Darstellung der fremden Macht verstärkte die deutsche Nationalidentität. Außerdem enthüllt eine Untersuchung der Schulbücher überraschende Ähnlichkeiten zwischen der deutschen Beschreibung von Rußland und den englischen und französischen Darstellungen des Nahen Osten. L'auteur de cet article analyse l'image de la Russie dans les manuels scolaires allemands d'histoire et de géographie. La pédagogie allemande du 19ème siècle faisait le lien entre les sciences naturelles et les sciences humaines; cette association fournit une preuve supplémentaire du fait que l'Etat-nation était perçu comme un organisme vivant. Alors que les différences régionales et confessionnelles existant entre les différents Etats allemands influençaient la présentation de l'histoire allemande, la description de la Russie était concordante. La Russie était dépeinte comme un empire barbare, arriéré et asiatique. La comparaison implicite, et souvent explicite des textes scolaires concernait la Russie et l'Allemagne. La représentation d'une puissance étrangère servait à renforcer l'identité allemande. En outre, l'analyse de ces manuels révèle des ressemblances étonnantes entre la perception de la Russie et les portraits français et anglais du Proche-Orient.
Keywords: dept.his; ⛔ No DOI found

Abolition and Antislavery: United States - Forbes, Robert P. (A Historical Guide to World Slavery, 1998)
Eminent scholars provide an overview of what we now know about slavery as an institution and way of life in cultures around the globe from ancient times to the present day. Drawing on the virtual explosion of empirical research and theoretical discussion on the subject over the past thirty years, many of the articles overturn conventional wisdom and illuminate little-known aspects of the subject, with essays on topics such as concubinage, eunuchs, and occupational mobility.
Keywords: dept.his

Slavery and the Evangelical Enlightenment - Forbes, Robert Pierce (Religion and the Antebellum Debate Over Slavery, 1998)
Keywords: 19th century; 19th century; Slavery; History; History / United States / 19th Century; Slavery and the church; Social Science / Ethnic Studies / African American Studies; Social Science / Sociology of Religion; United States; dept.his; faculty_collection

The Carswell affair: The politics of a Supreme Court nomination in the Nixon administration - Kalk, BH (American Journal of Legal History, 1998)
Keywords: dept.his

Book Review: Barbara Caine. English Feminism, 1780–1980 . New York: Oxford University Press. 1997. Pp. xvii, 336. 19.95 paper. ISBN 0-19-820434-5. - Beals, Polly (Albion, 1998)
Keywords: book.review; dept.his

Still stuck at sevastopol: the depiction of russia during the russo-japanese war and the beginning of the first world war in the german press - Paddock, Troy (German History, 1998)
Keywords: dept.his